Punish, seduce or persuade: an empirical assessment of anti-piracy interventions - Leeuw, H. B. M. (Eleven International Publishing, 2017)
An introduction to digital piracy -- Research methodology -- The scope and consequences of digital piracy -- How can the behaviour of digital pirates be explained? : a synthesis throught the lens of the situational action theory -- How to discourage digital pirates : focusing on anti-piracy interventions and their mechanisms -- An assessment of anti-piracy interentions : requirements for the three mechanisms -- Measuring the contributions of anti-priacy interventions and their mechanisms -- Changes in online search behavior after the implementation of an anti-priacy intervention : the Copyright alert system as a case study -- Conclusion and future outlook